2018
DOI: 10.2147/ott.s160493
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HHLA2, a member of the B7 family, is associated with worse survival in human colorectal carcinoma

Abstract: BackgroundColorectal carcinoma (CRC) is one of the most common malignancies, and immunotherapy has opened a new field of cancer treatment in recent years. Generally, CRC does not benefit from immunotherapy. HHLA2, a member of the B7 family, is a novel immune checkpoint molecule, and the prognostic value of HHLA2 in CRC patients and the association between HHLA2 expression and clinicopathological characteristics remains unknown.Materials and methodsThis study included 63 patients diagnosed with CRC, and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 32 publications
11
68
1
Order By: Relevance
“…Previous studies have shown that HHLA2 is negatively expressed in most human tissues, whereas it is overexpressed in a variety of cancers [12]. High HHAL2 expression is associated with poor survival in patients with breast cancer, colon cancer, clear cell renal cell carcinoma, gastric cancer, or osteosarcoma [12,13,[16][17][18]. Consistently, in this study, we found that HHLA2 is upregulated in BUC tissues compared with normal tissues, and high HHLA2 expression predicts poor survival in BUC patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous studies have shown that HHLA2 is negatively expressed in most human tissues, whereas it is overexpressed in a variety of cancers [12]. High HHAL2 expression is associated with poor survival in patients with breast cancer, colon cancer, clear cell renal cell carcinoma, gastric cancer, or osteosarcoma [12,13,[16][17][18]. Consistently, in this study, we found that HHLA2 is upregulated in BUC tissues compared with normal tissues, and high HHLA2 expression predicts poor survival in BUC patients.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have demonstrated that pathological grading and clinical tumor staging play pivotal roles are associated with lymph node metastasis and predict clinical prognosis of patients with BCa in clinical practice. It has been reported previously that high HHLA2 expression is correlated with metastasis in lung cancer, colorectal cancer, and osteosarcoma [13,18,19]. In this study, we found that a high expression of HHLA2 is also significantly associated with lymph node metastasis and HHLA2 is an independent factor of lymph node metastasis in BUC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Despite the significant advances of custom treatment method, the high migration and invasion capacity have been a bottle-neck for eliminating the mortality, which kept the 5-year survival rate of CRC under 12% [2][3][4]. In addition, several other factors were also identified to influence CRC prognosis, such as health-related quality of life [5], genome stability [6,7], aberrant gene expression [8,9], etc. However, the mechanism underlying CRC survival remains elusive, which impedes the improvement of CRC prognosis.…”
Section: Introductionmentioning
confidence: 99%